Applications and Techniques in Information Security : 6th International Conference, ATIS 2015, Beijing, China, November 4-6, 2015, proceedings /: 6th International Conference, ATIS 2015, Beijing, China, November 4-6, 2015, proceedings. (2015) - Unknown
No abstract available